The Meaning of the Bainai Night Tradition for the Community in Wedding Ceremonies in Jorong Lubuk Gadang Nagari Koto Tangah Koto Balingka District West Pasaman Regency - Nurmailisa, Nurmailisa; Elfemi, Nilda; Yuhelna, Yuhelna (QISTINA: Jurnal Multidisiplin Indonesia, 2024)
The malam bainai tradition is one of a series of activities in a marriage ceremony that puts inai on the hands of the bride and groom. In Jorong Lubuk Gadang, Nagari Lubuk Gadang, Koto Balingka District, West Pasaman Regency, the malam bainai tradition is the closing event in a series of weddings. In this tradition, inai is used as a symbol of prayer and hope for the happiness and welfare of the bride and groom in their married life. This study aims to analyze the meaning of the Malam Bainai tradition for the community in the marriage ceremony in Jorong Lubuk Gadang Nagari Koto Tangah, Koto Balingka District, West Pasaman Regency. phenomenological theory proposed by Alfred Schutz, (1961). This research uses a qualitative approach with descriptive type. The technique of withdrawing informants in this study was carried out by purposive sampling technique. Data collection methods were carried out by document study, non-participant observation, in-depth interviews. The data analysis used was interactive data analysis developed by Milles and Huberman (1992). The results of this study indicate that in the process of implementing malam bainai in the marriage ceremony in Jorong The tradition of malam bainai in Jorong Lubuk Gadang has a deep meaning, seen through two concepts of motifs from Alfred Schutz. At the stage of sounding the drum, wearing inai, and eating together, this tradition reflects the meaning of the Objective Motive (in order to motive), because these stages are used as a foothold by the community in undergoing the process to achieve blessing results in a series of events. While the stage of making wages is included in the category of because of motive, because this process is a part that has existed since before in the malam bainai event and cannot be changed, and reflects the deep beliefs inherited from the past by the community. The update in this study is malam bainai as a closing event held at the end of a series of events after the wedding is held.